PENGARU LITERASI KEUANGAN DAN MOTIVASI INVESTASI TERHADAP MINAT INVESTASI DI PASAR MODAL MAHASISWA PENDIDIKAN EKONOMI FKIP UNS - BADRAPURA, CHENY AGSNA; Sudarno; Dini Octoria (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study aimed to determine (1) the effect of financial literacy on student investment interests, (2) the effect of investment motivation on student investment interests, (3) The effect of financial literacy and investment motivation on student investment interests. This research was a quantitative descriptive study with a population of 154 students of economic education for the 2019 and 2020 academic year. The sampling technique used in this study was propoltional random sampling, producing a sample of 112 student respondents. Data was collected through a questionnaire distributed via the Google form link. The data analysis used was multiple linear regression analysis with SPSS 25. The results shown from this study were: First financial literacy had a positive effect on the investment interest for undergraduate students economid education of Sebelas Maret University as evidenced by a regression coefficient of 0,225, t count (4.025) > t table (1.65) and sig. (0.000) < 0.05. Second, investment motivation had a positive effect on the investment interest for undergraduate students economic education of Sebelas Maret University as evidenced by a regression coefficient of 0.117, t count (2.109) > t table (1.65), and sig. (0.037) < 0.05. Third, simultaneous financial literacy and investment motivation had a positive effect on the investment interest of undergraduate students economic education of Sebelas Maret University, as evidenced by the calculated F value (17.870) > F table (3.08) and the sig. (0.000) < 0.05.